Merry and bright [large type] : a novel - Macomber, Debbie (Random House Large Print, 2017)
Merry Smith is pretty busy these days. She's taking care of her family, baking cookies, decorating for the holidays, and hoping to stay out of the crosshairs of her stressed and by-the-book boss at the consulting firm where she temps. Her own social life is the last thing she has in mind, much less a man. Without her knowledge, Merry's well-meaning mom and brother create an online dating profile for her--minus her photo--and the matches start rolling in. Initially, Merry is incredulous, but she reluctantly decides to give it a whirl.